Barley whole exome capture: a tool for genomic research in the genus Hordeum and beyond. (24th August 2013) - Mascher, Martin; Richmond, Todd A.; Gerhardt, Daniel J.; Himmelbach, Axel; Clissold, Leah; Sampath, Dharanya; Ayling, Sarah; Steuernagel, Burkhard; Pfeifer, Matthias; D'Ascenzo, Mark; Akhunov, Eduard D.; Hedley, Pete E.; et al.
Summary Advanced resources for genome‐assisted research in barley (Hordeum vulgare) including a whole‐genome shotgun assembly and an integrated physical map have recently become available. These have made possible studies that aim to assess genetic diversity or to isolate single genes by whole‐genome resequencing and in silico variant detection. However such an approach remains expensive given the 5 Gb size of the barley genome. Targeted sequencing of the mRNA‐coding exome reduces barley genomic complexity more than 50‐fold, thus dramatically reducing this heavy sequencing and analysis load. We have developed and employed an in‐solution hybridization‐based sequence capture platform to selectively enrich for a 61.6 megabase coding sequence target that includes predicted genes from the genome assembly of the cultivar Morex as well as publicly available full‐length cDNAs and de novo assembled RNA‐Seq consensus sequence contigs. The platform provides a highly specific capture with substantial and reproducible enrichment of targeted exons, both for cultivated barley and related species. We show that this exome capture platform provides a clear path towards a broader and deeper understanding of the natural variation residing in the mRNA‐coding part of the barley genome and will thus constitute a valuable resource for applications such as mapping‐by‐sequencing and genetic diversity analyzes.